(3QSGdI aj Yde GdSdhcs - (3GdocrHQi GdpNjhbj GdNhGQRej, CHh GdLfGH, fLe GdOjf, CMeO Hf YeQ Hf eMqeO, J(B618(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj jYde ejcGFjd GdHMGQ heKGbjd GdLHGds
(3BNQgG (B:s
(3eOQSJj bdHj JcQGQ PfHj aj Yde JbOjSj faSj EHdjS JLQHJgG fYhP HGddg ef TQ EHdjSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 185s
(3eYLe GdeDdajf(B: 1 / 218s
(3cTa GdXfhf(B: 1 / 872s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs